Analisis Determinan Kerusakan Infrastruktur Jalan Berbasis Persepsi Masyarakat dan Implikasinya Terhadap Kebijakan Pembangunan Wilayah Long Pejeng Kutai Timur - Gina Riska Yaret; Sutriani Sutriani; Aisyah Trees Sandy; Arum Sekar Kedhaton (Jayapangus Press, 2026)
The damage to road infrastructure in East Kutai Regency, particularly in Long Pejeng Village, indicates a gap between the region's economic potential and the low quality of basic infrastructure, impacting community mobility and socio-economic activities. However, the current approach to infrastructure development tends to be top- down and often ignores local perspectives, even though the experiences of the community as the primary users are a crucial source of information for understanding the causes of damage. This study aims to analyze community perceptions of the determinants of road damage and identify the dominant factors that emerge in the narratives of residents' experiences. The method used is a qualitative descriptive approach through in-depth interviews, observation, and documentation of 10 key informants. The results show that road damage is influenced by several main determinants, namely: (1) low material quality due to limited village budget; (2) construction that does not meet technical standards such as material composition and layer thickness; (3) vehicle load pressure that exceeds road capacity; and (4) environmental factors such as rainfall, waterlogging, and topographic conditions that accelerate degradation. These findings indicate that material and budget factors are the most dominant determinants, which are then reinforced by technical and environmental factors, forming a recurring cycle of damage. This situation has resulted in increased transportation costs, disrupted community mobility, and reduced regional connectivity. The study concluded that road damage is multidimensional, necessitating integrated development policies that adapt to local conditions and are supported by improved technical quality, strengthened budgets, and community participation in development planning.